AKUNTANSI SYARIAH UNTUK PRODUK WADIAH YAD DHAMANAH PADA KOPERASI SYARIAH KSPPS BINA SYARIAH UMMAH BANJARWATI PACIRAN LAMONGAN - Abdillaika Martiwi, Wanala; Nur Rohmawati, Ismy Tsaniyah; Mamdukh, Muhammad; Nabila Putri, Primadia; Latifah, Eny (JISEF : Journal Of International Sharia Economics And Financial, 2022)
The purpose of this study was to determine sharia accounting practices for Wadiah Yad Dhamanah  products for savings products at KSPPS Bina Syariah Ummah Banjarwati Paciran Lamongan. The research method is descriptive qualitative method using triangulation data analysis by combining documentation, observation and interview instruments. The results of this study show the application of savings products that use the principle of Wadiah Yad Dhamanah  at KSPPS Bina Syariah Ummah. The application of wadiah products using names includes: Sitakwa, Simpendik (education savings), Siharoh (Hajj and Umrah savings), Sihara (holiday savings), sitabah (sacrificial savings and savings, and futures welfare savings. Services provided by KSPPS Bina Sharia Ummah for products that use the principle of Wadiah Yad Dhamanah  is to provide savings facilities that can be withdrawn at any time needed and are still within relatively easy reach.